1995
DOI: 10.1143/jjap.34.l789
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Atomic Force Microscopy Image Variations along the Surface Normal: Presence of Possible Resolution Limit in the Attractive Force Range

Abstract: Variations of atomic force microscopy (AFM) images as tip-sample distance is varied were examined using a newly developed AFM simulation code ACCESS (AFM simulation Code for Calculating and Evaluating Surface structures) with a Morse-type pairwise potential. A model system consisting of a single atom tip (an “ideal" AFM tip) and a face-centered cubic (fcc) (100) surface with or without point defect showed perfect atomic resolution when scanning was performed in the repulsive force range. In the attractive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Figure 4 shows the simulated results for each of the three tip orientations. Weaker applied force means longer tip-to-sample distances, and our earlier calculations 13,14 indicated that this necessarily means the loss of resolution. For the single-atom tip (θ s orientation) no resolution loss is observed, and the atom-resolved image is still obtained (Figure 4a).…”
Section: Determination Of the Vertical Positions Of K + Ionsmentioning
confidence: 85%
See 2 more Smart Citations
“…Figure 4 shows the simulated results for each of the three tip orientations. Weaker applied force means longer tip-to-sample distances, and our earlier calculations 13,14 indicated that this necessarily means the loss of resolution. For the single-atom tip (θ s orientation) no resolution loss is observed, and the atom-resolved image is still obtained (Figure 4a).…”
Section: Determination Of the Vertical Positions Of K + Ionsmentioning
confidence: 85%
“…Loading force apparently has a strong influence on the observed images, by governing the tip−sample distance. The distance in turn governs the resolution, particularly for isotropic potentials. , Thus these images may take various forms depending on the applied force, or tip−sample distance. It should be noted that the absolute value of the force examined in this simulation is not important, since it may strongly depend on the size of the simulated tip …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simulation of AFM imaging of the surface was performed following a previously reported method, using an algorithm similar to the previously developed AFM simulator ACCESS under two-dimensional periodic boundary conditions parallel to the sample surface. With a model AFM tip consisting of a Si(OH) 4 cluster the topmost cleaved plane of heulandite(010) was scanned.…”
Section: Methodsmentioning
confidence: 99%
“…3(a)) gives a better atomic contrast, which is in good agreement with results from simulation. 6,7 The Fourier transform of the unfiltered image shown in Fig. 3(a) is given in Fig.…”
Section: Nanostructuresmentioning
confidence: 99%